Relation Between Hizbut Tahrir Indonesia and Terror Group - Zopfan Aseanata Bayudhita (Sekolah Tinggi Ilmu Kepolisian, 2020)
Abstract Hizbut Tahrir Indonesia, one of the most controversial organization in Indonesia was long accused supporting radicalism and intolerant movement in society. With soft approach and persuasive skill they used, Hizbut Tahrir Indonesia attract some people and groups to join with them. They promoting a better world under one Islamic Caliphate. Hizbut Tahrir Indonesia had close relation with Hizbut Tahrir and Ikhwanul Muslimin in Middle East. They also adopted their propaganda and movement by spreading their ideology and targeting youth generation. However, their link with some violence and radical movement in Indonesia pushed them to being banned by Indonesian Government. As court got some evidence of their involvement on those activities, Indonesia Government officially banned and dismissed Hizbut Tahrir Indonesia in 2017. Keywords : Hizbut Tahrir Indonesia; terrorism; radicalism; intolerant; caliphate Abstrak Hizbut Tahrir Indonesia, salah satu organisasi paling kontroversial di Indonesia telah lama dituduh mendukung radikalisme dan gerakan intoleran di masyarakat. Dengan pendekatan lunak dan keterampilan persuasif yang mereka gunakan, Hizbut Tahrir Indonesia menarik beberapa orang dan kelompok untuk bergabung dengan mereka. Mereka mempromosikan dunia yang lebih baik di bawah satu kekhalifahan Islam. Hizbut Tahrir Indonesia memiliki hubungan dekat dengan Hizbut Tahrir dan Ikhwanul Muslimin di Timur Tengah. Mereka juga mengadopsi propaganda dan gerakan mereka dengan menyebarkan ideologi mereka dan menargetkan generasi muda. Namun, hubungan mereka dengan beberapa kekerasan dan gerakan radikal di Indonesia mendorong mereka untuk dilarang oleh Pemerintah Indonesia. Ketika pengadilan mendapatkan beberapa bukti keterlibatan mereka dalam kegiatan tersebut, Pemerintah Indonesia secara resmi melarang dan memberhentikan Hizbut Tahrir Indonesia pada tahun 2017. Kata kunci: Hizbut Tahrir Indonesia; terorisme; radikalisme; intoleran; Khalifah